2023
DOI: 10.3389/fmicb.2023.1100873
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome types of colorectal tissue are potentially associated with the prognosis of patients with colorectal cancer

Abstract: As the second leading cause of cancer worldwide, colorectal cancer (CRC) is associated with a poor prognosis. Although recent studies have explored prognostic markers in patients with CRC, whether tissue microbes carry prognostic information remains unknown. Here, by assessing the colorectal tissue microbes of 533 CRC patients, we found that Proteobacteria (43.5%), Firmicutes (25.3%), and Actinobacteria (23.0%) dominated the colorectal tissue microbiota, which was different from the gut microbiota. Moreover, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Harrold and colleagues ( 48 ) showed an increased abundance of the genera Bacillus and Lactobacillus in azure-winged magpies that received dietary supplementation with putrescine. Overall, we found that putrescine increased the Firmicutes / Bacteroidetes ratio, and a higher Firmicutes/Bacteroidetes ratio is linked to better survival in patients with colorectal cancer ( 51 ). In the phylum Firmicutes , we found an increase in the Limosilactobacillus genus in which Limosilactobacillus fermentum has been reported to produce peptidoglycan with anti-proliferative properties ( 52 ) and Limosilactobacillus reuteri has been shown to suppress colorectal tumorigenesis ( 53 ).…”
Section: Discussionmentioning
confidence: 95%
“…Harrold and colleagues ( 48 ) showed an increased abundance of the genera Bacillus and Lactobacillus in azure-winged magpies that received dietary supplementation with putrescine. Overall, we found that putrescine increased the Firmicutes / Bacteroidetes ratio, and a higher Firmicutes/Bacteroidetes ratio is linked to better survival in patients with colorectal cancer ( 51 ). In the phylum Firmicutes , we found an increase in the Limosilactobacillus genus in which Limosilactobacillus fermentum has been reported to produce peptidoglycan with anti-proliferative properties ( 52 ) and Limosilactobacillus reuteri has been shown to suppress colorectal tumorigenesis ( 53 ).…”
Section: Discussionmentioning
confidence: 95%
“…Another emerging tool, circulating tumor DNA (ctDNA) analysis, has shown promise in identifying minimal residual disease [ 67 ], which results in a higher risk of recurrence for patients and may require closer surveillance or additional treatment options. Furthermore, the study of the gut microbiome is also a recent topic of interest for the assessment of both tumor onset and recurrent disease [ 68 , 69 ]. Lastly, exploring the tumor microenvironment [ 40 , 70 ], such as TILs, tumor-associated fribroblasts and stromal characteristics, and understanding the interactions between tumor cells and their microenvironment might provide valuable prognostic information.…”
Section: Discussionmentioning
confidence: 99%
“…Despite reduced gut microbiota diversity, an abundance of Proteobacteria, Streptococcus, Campylobacter, and Moraxellaceae was found in both cancer bearing groups [36] . Interestingly, Proteobacteria, Streptococcus, and Campylobacter have all been linked to colorectal cancer [38] , [39] , [40] . In the non-cancer controls, Megamonas , Akkermansia, Clostridia, Gemmiger, and Paraprevotella were significantly more abundant [36] .…”
Section: The Gut Microbiome and Cancer In The Bonementioning
confidence: 99%